SPE Western North American and Rocky Mountain Joint Meeting 2014
DOI: 10.2118/169547-ms
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Encapsulated Oil as an Additive to Water-Based Drilling Fluids: Operational Improvements in Lubricity, Drag, and ROP

Abstract: Description of Proposed PaperAs the drilling industry moves towards extended-reach wells in more challenging formations, the need to identify operational solutions (e.g., drilling fluids/lubricity additives) to reduce friction, torque, and drag has become more important. Additionally, as the industry looks to maximize the use of water-based drilling fluids (to benefit from lower drilling fluid costs and improved environmental profile), the need to find novel additives that can improve lubricity has become more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The deformation changes in its magnitude by an increment of ∆z, which can be evaluated using Equation (7). In Figure 11, z'(t) is the actual magnitude of the elastic deformation of an asperity in the first step of motion and can be described by the following relationship:…”
Section: Asperity Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The deformation changes in its magnitude by an increment of ∆z, which can be evaluated using Equation (7). In Figure 11, z'(t) is the actual magnitude of the elastic deformation of an asperity in the first step of motion and can be described by the following relationship:…”
Section: Asperity Deformationmentioning
confidence: 99%
“…These methods have included chemical methods and mechanical methods [6]. The chemical methods have been focused on the reduction of the friction factor between drill strings and wellbores [7]. The properties of the mud cake were modified or lubricants were added into the drilling fluid [8].…”
Section: Introductionmentioning
confidence: 99%
“…The tools fall into two categories, mechanical method and chemical method. 6 The chemical technologies mainly are lubricants additive in the drilling mud. 7,8 The mechanical drag reduction methods are more suitable than chemical method due to low-cost and environment friendly.…”
Section: Introductionmentioning
confidence: 99%
“…[14] developed water-based mud system that approaches the performance of oil-based mud using starch lubricant composition, they reported an approximate coeficient of friction values close to that of an average oil-based mud; Alford et al [15] reported work on systemmatic investigation of both lubricity characteristics of sillicate drilling fluids and the effect of silicate-base systems on the formation production and evaluation, their results show promising applications. A novel biotechnological method was developed by Schuh et al [16] using encapsulating oil in polysaccharride-based polymer that delivers high pressure lubricity, it was designed to improve lubricity in horizontal wells using non-reactive lubricant product additives. Recently, Nano graphene application in improving drilling fluids performance was reported by Taha and Lee [17].…”
Section: Introductionmentioning
confidence: 99%